Secularisation and the Future of Christianity - Martin, David (Journal of contemporary religion, 2005)
The article is not an account of a debate. Rather it summarises a position arrived at over 40 years with respect to Secularisation. It deals with master narratives, the differences between Catholic and Protestant trajectories, with European exceptionalism, and the varying consequences of spirituality' and individualism.